Effort To Provide Supplementary Food (PMT) As A Measure To Preventt And Handl Stunting In Pendua Village - Multian, Dian; Hasanah, Ihsan; Lestari, Dewi Ayu; Jannah, Miftahul; Hamdani, Muh (Abdi Masyarakat, 2025)
Stunting is a chronic nutritional problem that remains prevalent in Indonesia, particularly in rural areas like Pendua Village. This condition is caused by long-term nutritional deficiencies and is often linked to poverty, inadequate parenting, and limited access to health services. This study aims to analyze efforts to provide Supplementary Feeding (PMT) as a strategy for preventing and managing stunting in Pendua Village. The method used was a qualitative descriptive approach, with data collection through observation, interviews with Posyandu (Integrated Service Post) cadres, health workers, and mothers of toddlers, and documentation studies. The results indicate that the PMT program provided to toddlers at risk of stunting has had a positive impact on improving children's nutritional status. The PMT provided is based on local foods such as mung beans, eggs, and vegetables, tailored to children's nutritional needs. Furthermore, regular nutrition education activities for parents have strengthened the program's effectiveness. However, challenges remain, such as limited funding, varying levels of maternal knowledge, and program sustainability.In conclusion, PMT is an effective intervention in preventing and managing stunting, but it requires multisectoral support and active community involvement to achieve optimal and sustainable results.